Hybrid spectrum sensing using energy detector and cyclostationary feature detection with wireless distributed computing concept - Alfaqawi, Mohammed I.M (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Recently, many studies forecast a crisis of scarcity will face the commercial electromagnetic spectrum due to the rapid growing of the wireless communication technologies, the fixed allocation policies of the spectrum and the inefficiently utilization by the channels owner or the primary user (PU). Cognitive radio (CR) technology is considered as the solution to spectrum scarcity by enabling visitors or secondary users (SU) to efficiently sense the PU channels. Various techniques are proposed to sense PU. The most important factor in distinguishing between these techniques is the detection accuracy. However, computational complexity, consumed power and processing time are increasing proportionally with increasing the accuracy rate. Therefore, this research aims to solve the problem of the increased computational complexity and sensing time with high probability of detection. In order to achieve this aim, a hybrid spectrum sensing algorithm is proposed by introducing two models to compute the energy and by performing wireless distributed computing (WDC) with cyclostationary feature detection. The proposed hybrid algorithm is analyzed by proving the algorithm mathematically and by simulation using MATLAB. The analysis considered additive white Gaussian noise (AWGN) channel between the cooperated CRs and the multipath is represented by Rayleigh fading. The results found that when the workload distributes between four cooperated CRs, the accuracy of the improved algorithm is affected by the channel variations. On the other hand, the computational complexity the improved algorithm is reduced to 50% and the processing time reduction to around 20%.